Salmon Intake Intervention in the Vulnerable Group of Young Polish Women to Maintain Vitamin D Status during the Autumn Season - Zofia Utri; Dominika Głąbska (Sustainability, 2020)
Fish products are the main dietary source of vitamin D, but due to a low fish intake in the majority of European countries, an inadequate vitamin D intake is common, especially in the vulnerable group of young women for whom it is essential for the osteoporosis prevention. The aim of the presented study was to assess the possibility of applying salmon intake intervention for maintaining vitamin D status in young Polish women during the autumn season, in which in Poland there is not enough sunshine exposure to generate skin synthesis. The dietary intervention within VISA Study (Vitamin D In Salmon) comprised eight weeks of daily consumption of 50 g of Atlantic salmon and was conducted in a group of 47 women aged 20–30 years. Within the study, their changes of total serum 25-hydroxyvitamin D (25(OH)D) levels were analyzed and the effectiveness of the intervention depending on age, body mass index (BMI), and baseline 25(OH)D were assessed. Until the 4th week, 25(OH)D in the studied group decreased from 57.1 nmol/L to 39.9 nmol/L (p < 0.0001), but afterward it increased until the 8th week to 54.1 nmol/L (p = 0.0005), contributing to results not differing from the baseline (p = 0.7964). At the same time, the share of respondents characterized by an inadequate vitamin D status increased until the 4th week, but afterward, it decreased until the 8th week (p = 0.0002). Neither the age (in the assessed range), nor the BMI influenced 25(OH)D during the study, but only the baseline 25(OH)D was correlated with the BMI (p = 0.0419; R = −0.2980). The baseline 25(OH)D was associated with its levels during the intervention, as well as with 25(OH)D change from the baseline values (p < 0.0001). It may be concluded that, in spite of the initial decline of the 25(OH)D observed (probably connected to the starting time of the study), afterward the salmon intake intervention contributed to its increase, while the baseline 25(OH)D status was an important determinant of the intervention effectiveness during the autumn season.